Transcendental Communication in MH Saifurrahmi's Nerve Reflex Therapy: An Epistemological Perspective of Irfani - Gusli bambang irawan (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Sekolah Tinggi Agama Islam As-Sunnah, 2023)
Transcendental communication is a relatively new concept in the realm of communication studies. It refers to communication between a servant and God, characterized as transcendent or vertical. One instance of this is observed in the phenomenon of nerve reflex therapy by MH Saifurrahmi, where transcendental communication is utilized. Transcendental communication is also a recent development in the field of communication studies. This article examines the transcendental communication phenomenon present in MH Saifurrahmi's nerve reflex therapy in Mayang, Jambi City. The research adopts a qualitative descriptive approach, collecting data through observations, interviews, and documentation. The research findings reveal that in the nerve reflex therapy conducted by MH Saifurrahmi in Mayang, Jambi City, the phenomenon involves the use of